Retention, distribution, and excretion of lead by the rat after intravenous injection. - Morgan, A (1977)
The distribution and excretion of lead was studied during a period of about a week after a single intravenous injection of 203Pb as chloride accompanied by less than 1 microng of lead carrier. The peak concentration in venous blood was reached after about an hour when it contained 35 to 40% of the administered activity. The subsequent decline in concentration was much more rapid than is observed in man. The main storage organs were the kidneys and bone. Initially, 20% of the dose could be accounted for in the kidney and the biological half-life was about 100 hours. The level in bone built up rapidly at first and then more slowly. After a week, between 25 and 30% of the dose was present in bone.